The Influence of Company Size, Leverage, Sales Growth, and Financial Distress on Tax avoidance Moderated by Independent Commissioners in Property and Real Estate Sector Companies Listed on IDX in 2019-2022 - Utami, Annisa Rianti; Danarsari, Dwi Nastiti (Eduvest - Journal of Universal Studies, 2023)
This research aims to determine the influence of company size, leverage, sales growth, and financial distress on tax avoidance moderated by independent commissioners in property and real estate sector companies listed on the IDX for the 2019-2022 period. The independent variables in this research are company size, leverage, sales growth, and financial distress. The dependent variable in this research is tax avoidance. The moderating variable in this research is independent commissioner. This population study includes companies listed on the IDX in 2019-2022. The analysis technique used is panel data regression analysis with eviews v.10 software and Microsoft Excel. The results of this research show that company size has no significant effect on tax avoidance, leverage has a positive and significant effect on tax avoidance, sales growth has no significant effect on tax avoidance, financial distress has a negative and significant effect on tax avoidance. independent commissioners have a positive and significant effect on tax avoidance, independent commissioners can moderate company size on tax avoidance, independent commissioners are able to moderate leverage on tax avoidance. Independent commissioners cannot moderate sales growth against tax avoidance. Independent commissioners cannot moderate financial distress towards tax avoidance in property and real estate sub-sector companies listed on the IDX for the 2019-2022 period.